I Am Mother : Thoughts & Quotations by Women About Motherhood - Alicat Publishing (South Melbourne Alicat Publishing, 2012)
Motherhood can be a woman's greatest joy, her deepest sadness, her biggest frustration and her most celebrated accomplishment all rolled into one. This book features a beautiful collection of modern thoughts and quotations all about mothers and motherhood.
Include Illustration
Keywords: Motherhood -- Mothers